FACTORS OF FORMATION AND DEVELOPMENT OF STAGE SPEECH SKILLS IN PERFORMING ARTS (World Conference on Agricultural and Earth Sciences, 2026)
This article analyzes the theoretical foundations, methodological approaches and practical experience of developing stage speech skills in students of the performing arts. Also, scientific considerations are made based on the traditions of the national theater school, modern pedagogical technologies, and the Basic rules of phonetics and linguistics in the formation of stage speech.
Keywords: Performing arts, stage speech, acting skills, speech skills, intonation, diction, pronunciation, stage culture, speech technique, pedagogical technology, innovative education.